2009
DOI: 10.1177/230949900901700322
|View full text |Cite
|
Sign up to set email alerts
|

Review Article: Patellar Instability after Total Knee Arthroplasty

Abstract: Patellar instability after total knee arthroplasty (TKA) is a serious complication that impairs functional outcome and may lead to revision surgery. Its aetiology can be related to the surgical technique and component positioning, extensor mechanism imbalance, and other causes. After TKA, the presence of anterior knee pain, especially during stressful activities, is indicative of patellar instability. Diagnosis can be made by radiological evaluation of the patella position, alignment, and component fixation. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 56 publications
(63 reference statements)
0
28
0
3
Order By: Relevance
“…This condition reduces patient satisfaction and limits patient post-operative activity and is a common cause of revision surgery. 1,2 It was reported that 5-10% of patients had anterior knee pain after TKR. 3 Resurfacing or patellar non-resurfacing in TKR is still a controversial topic among surgeons.…”
Section: Introductionmentioning
confidence: 99%
“…This condition reduces patient satisfaction and limits patient post-operative activity and is a common cause of revision surgery. 1,2 It was reported that 5-10% of patients had anterior knee pain after TKR. 3 Resurfacing or patellar non-resurfacing in TKR is still a controversial topic among surgeons.…”
Section: Introductionmentioning
confidence: 99%
“…Eski tasarım protezlerle yapılan total diz artroplastilerinden sonra %10-35 arasında patellada yarı çıkık veya tam çıkık görülme-sine karşın günümüzde revizyon gerektiren semptomatik instabilite %1-4 arasında bildirilmiştir. [11][12][13] Nedenleri, komponentlerin uygun olmayan dizilimi, ekstansör mekanizmaya verilen hasarlar, gergin retinakulum, protezin tasarımı ve valgus dizdir (Tablo 2). Dizin normal anatomik ve kinematik yapılarının ilişkisini bozarak lateral retinakulum veya Q (kuadriseps) açısının artışına neden olan her türlü işlem laterale doğru artmış kas gücü vektörüne yol açarak instabilite oluşturabilir.…”
Section: Patellar İnstabi̇li̇teunclassified
“…Maltracking can be related to an insufficient soft tissue balancing, patello-femoral joint overstuffing, asymmetrical resection of the patella, or poor component positioning [70,72]. Implant design may also play an important role in patellar maltracking [73,74].…”
Section: Patello-femoral Instability and Maltrackingmentioning
confidence: 99%
“…Patellar instability can be caused by various surgical errors like residual valgus alignment, patella alta, malrotation, medial translation of the femoral component, asymmetric patellar resection, excessive lateral placement of the patellar button, and improper soft tissue balancing [70,75].…”
Section: Patello-femoral Instability and Maltrackingmentioning
confidence: 99%
See 1 more Smart Citation